2023
DOI: 10.3389/fpsyg.2023.1071938
|View full text |Cite
|
Sign up to set email alerts
|

Stress and depressive symptoms in university students in Hong Kong under the pandemic: Moderating effect of positive psychological attributes

Abstract: IntroductionThere are very few studies examining the psychological well-being of university students in Hong Kong under the COVID-19 pandemic. Besides COVID-19-related stress, the “social event” in 2019-2020 has caused significant stress in young people. As such, we attempted to answer several research questions in this paper. First, what are the relationships between stresses (COVID-19 and “social event” related stresses) and psychological well-being indexed by depressive symptoms? Based on the stress and cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 90 publications
1
2
0
Order By: Relevance
“…This combined approach facilitates a more comprehensive and nuanced understanding of the diverse elements that contribute to students' well-being and resilience. By adopting this framework, results of this study strengthen the argument that various factors within the ecological system play risk and protective roles in shaping the mental health of university students, with a particular emphasis on personal factors as well as the influence of family, peers, and the community (Shek et al, 2023b). In addition, the study is consistent with strength-based perspectives, which highlight the importance of internal and external assets in promoting healthy development among adolescents (Benson, 2007).…”
Section: Implications Limitations and Conclusionsupporting
confidence: 77%
“…This combined approach facilitates a more comprehensive and nuanced understanding of the diverse elements that contribute to students' well-being and resilience. By adopting this framework, results of this study strengthen the argument that various factors within the ecological system play risk and protective roles in shaping the mental health of university students, with a particular emphasis on personal factors as well as the influence of family, peers, and the community (Shek et al, 2023b). In addition, the study is consistent with strength-based perspectives, which highlight the importance of internal and external assets in promoting healthy development among adolescents (Benson, 2007).…”
Section: Implications Limitations and Conclusionsupporting
confidence: 77%
“…It focuses on enhancing the well-being and optimal functioning of individuals (Verma, 2022). Central to this field are elements such as hope, optimism, resilience, emotional competence, flourishing, and life satisfaction (Shek et al, 2023). Research in this domain includes multicomponent interventions aimed at improving mental health and reducing psychological issues like depression, anxiety, and stress among young people (Tejada-Gallardo et al, 2020).…”
Section: Positive Psychologymentioning
confidence: 99%
“…Research also demonstrated that life satisfaction, resilience, emotional regulation, flourishing, and beliefs regarding adversity have significant moderating influences on the relationship between stress and depression. This suggests that these positive psychological attributes can mitigate the adverse effects of stress on depression [ 19 ]. Along the same lines, there are still many aspects of character strengths and inner strengths that remain unexplored or have yet to be thoroughly examined, such as gratitude, self-regulation, generosity, and loving-kindness.…”
Section: Introductionmentioning
confidence: 99%